2012
DOI: 10.1371/journal.pone.0036042
|View full text |Cite
|
Sign up to set email alerts
|

Font Size Matters—Emotion and Attention in Cortical Responses to Written Words

Abstract: For emotional pictures with fear-, disgust-, or sex-related contents, stimulus size has been shown to increase emotion effects in attention-related event-related potentials (ERPs), presumably reflecting the enhanced biological impact of larger emotion-inducing pictures. If this is true, size should not enhance emotion effects for written words with symbolic and acquired meaning. Here, we investigated ERP effects of font size for emotional and neutral words. While P1 and N1 amplitudes were not affected by emoti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
61
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(73 citation statements)
references
References 25 publications
11
61
1
Order By: Relevance
“…In addition, the ERP effects of the font size and type for L1 and L2 words should be taken into consideration. In this regard, Bayer et al (2012) found that larger font size leads to an increase of early emotion effects in ERPs for written words. Font size of L1 and L2 words was well-controlled in our study.…”
Section: Discussionmentioning
confidence: 94%
“…In addition, the ERP effects of the font size and type for L1 and L2 words should be taken into consideration. In this regard, Bayer et al (2012) found that larger font size leads to an increase of early emotion effects in ERPs for written words. Font size of L1 and L2 words was well-controlled in our study.…”
Section: Discussionmentioning
confidence: 94%
“…As forgas noted, emotions "appear to influence what we notice, what we learn, what we remember, and ultimately the kinds of judgments and decisions we make" [22, p. 273]. In the context of written communication, previous research has indicated that emotional stimuli in terms of emotion words or emotional framing of messages may elicit extensive cognitive processes such as attention (e.g., [7,40,62]). An increased level of cognitive involvement may in turn lead to a higher likelihood of behavioral response to emotional stimuli in terms information sharing (e.g., [31,47,56,58]).…”
Section: Influence Of Emotions On Information Sharingmentioning
confidence: 99%
“…It has been shown that affective information could be transferred through computer-mediated communication (CMC) [29]. Results from studies on SNS, weblogs, discussion forums, online news portals, or other contexts indicated that the affective dimensions of messages (both positive and negative sentiment) could trigger more cognitive involvement in terms of attention (e.g., [7,40,62]) as well as higher levels of arousal (e.g., [8]), which in turn have an influence on feedback and reciprocity (e.g., [19,34,63]), participation (e.g., [38]), and social sharing behavior (e.g., [9]). …”
mentioning
confidence: 99%
“…In the context of written verbal communication, previous research has indicated that emotional stimuli in terms of emotion words or emotional framing of messages may elicit extensive cognitive processes such as attention (e.g. Smith & Petty 1996;Kissler et al 2007;Bayer et al 2012). A higher level of cognitive involvement may, in turn, lead to a higher likelihood of behavioral response to emotional stimuli in terms information sharing (e.g.…”
Section: Sentiment and Information Diffusion On Twittermentioning
confidence: 99%